The Influence of Competence, Work Motivation and Work Experience on Teacher Performance - Yelipele, Samsul; Ibrahim, Muhdi B. Hi; Mustajab, Duta (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This research aims to analyze, identify, and explain the effect of competence, work motivation, and work experience on teachers' performance at the State Tsanawiyah Madrasah (MTSN) Koya Barat, Jayapura City, Papua Province. Research Design and Methodology: This associative research used 36 respondents, representing 100% of the population through total sampling or saturated samples. Data were collected and analyzed using partial and simultaneous tests to assess the impact of the independent variables on teacher performance. Findings and Discussion: The study found that competence, work motivation, and work experience positively and significantly affect teachers' performance at MTSN Koya Barat. The Adjusted R² value of 0.651 indicates that these variables explain 65.1% of the variance in teacher performance. The remaining 34.9% is influenced by other factors not included in this model, such as education, training, work environment, discipline, leadership, and technology utilization. Among the variables, competence emerged as the most dominant factor, with a Standardized coefficient beta of 0.623 and a t-value of 7.984, indicating a significant level of influence compared to work motivation and work experience. Implications: The findings suggest that enhancing teacher competence through targeted training and development programs is crucial for improving teacher performance. Additionally, boosting work motivation and leveraging work experience can further optimize educational outcomes. Policymakers and educational leaders should focus on these areas to create supportive environments that foster teacher growth and effectiveness.